Experience Of Police Officers In Providing Victim's First Aid Traffic Accident In Trenggalek - Anggraini, Novita Ana; Fawzi, Alfian; Fazrin, Intan; Wulandari, Suci (Journal of Global Research in Public Health, 2019)
Police officer holds a very important role in giving first aid to the traffic crash victim if there are limitations of medical officer to provide help. They certainly have special experience in giving first aid to traffic crash victims besides their main duties as police officer. This research was used qualitative phenomenological design to explore and to elucidate in-depth about the experience of police officers in providing first aid for traffic crash victims. There are 4 participants who served in traffic accident unit police station district of Trenggalek. This study Instruments are including researcher as core instruments and other supporting tools in the form of in-dept interview guide sheets, tape recorder, notebooks and camera. Data collected through a comprehensive interview and processed into transcript then analyzed. The research results obtained by two major themes, victim identification dan first aid skills. The conclusion is that the police officer to provide help to the victims to save their lives. Therefore, it is necessary to increase the ability of the police to conduct and recognize the condition of victims of traffic accidents and the ability to provide first aid to victims of traffic accidents. So that the safety of accident victims the midle of limited medical services outside the hospital increases